Heteropolyacids supported on mesoporous AlSBA-15 as efficient catalysts for esterification of levulinic acid - Lucas, Nishita; Gurrala, L.; Athawale, Anjali (Journal of Porous Materials, 2019)
A comparative study of different heteropoly acids supported on mesoporous AlSBA-15 for the synthesis of ethyl levulinate has been undertaken for the first time. The catalysts were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, inductively coupled plasma-optical emission spectrometry, thermo gravimetric analysis, temperature programmed desorption of NH3 and N-2 sorption studies. Insights into crucial parameters for the esterification reactions are also furnished. A distinct correlation was observed between acid density and conversion revealing that the distribution of acidic sites and their accessibility by the reactant moieties plays an important role in determining the overall activity. The effects of various reaction parameters were investigated to enhance the catalytic activity and yield of ethyl levulinate. Under the optimized conditions, levulinic acid conversion of 87.4 mol% and ethyl levulinate selectivity of 100% could be obtained with silicotungstic acid supported on AlSBA-15.